Perfil Sociodemográfico de un Grupo de Trabajadoras Sexuales de Puerto Rico - Rodríguez-Figueroa, Judith; Irizarry-Castro, Alma; Alegría, Margarita; Vera, Mildred; Pérez-Perdomo, Rosa (Puerto Rico Health Sciences Journal, 2015)
see manuscript